Acute Fatty Liver of Pregnancy and its Differentiation from Other Liver Diseases in Pregnancy - Maier, J. T.; Schalinski, E.; Häberlein, C.; Gottschalk, U.; Hellmeyer, L. (Geburtshilfe und Frauenheilkunde, 2015)
Background: There are a number of threatening liver diseases that occur during pregnancy. Acute fatty liver of pregnancy is a rare disease associated with high maternal and foetal mortality. Case Report: We report on a young gravida 1 woman who presented to our level 1 perinatal centre in the 36 + 5 week of pregnancy with an isolated elevation of transaminases together with diffuse upper abdominal complaints. After comprehensive diagnostic work-up we performed an emergency delivery by Caesarean section. This was followed by interdisciplinary management. Discussion: The differentiation from other liver diseases seems not to be obvious in all cases. Here we consider the following differential diagnoses: hyperemesis gravidarum, intrahepatic gestational cholestasis, preeclampsia, HELLP syndrome. Conclusion: Rapid diagnosis and delivery as well as interdisciplinary aftercare are necessary in order to reduce maternal and foetal mortality.
Keywords: acute fatty liver of pregnancy; HELLP syndrome; premature birth; high-risk pregnancy; disseminated intravascular coagulation; maternal mortality